Marketing of Grapes in Karnataka: A Case of Bangalore and Bijapur District - Sowmya Shankar, B.; Devajar, M.; Satish Chandra Rangaswamy, R. (Indian Journal of Marketing, 2008)
In India we are producing all varieties of grapes; Indian climatic condition is well suites for production of good quality grapes. At the same time our productivity is also considerably good. Besides increasing productivity and production of grape, creation of integrated physical distribution network for grape crop is the need of the hour. Fruits marketing in India are in a highly deplorable condition. The fruit growers in India are at the mercy of the middlemen. Even today the marketing system and channels of distribution, for fruits in India is traditional in nature, usually the standing crop is sold to a pre-harvest contractors. These contractors take care of the crop and sell it in a wholesale market where commission agents and wholesalers take a major share in that. The number of middlemen in the channel is generally more; the study discloses a very interesting picture with a changed situation in Bangalore and Bijapur market.